2011
DOI: 10.1017/s095026881100210x
|View full text |Cite
|
Sign up to set email alerts
|

First report of methicillin-resistantStaphylococcus aureusCordobes/Chilean clone involved in nosocomial infections in Brazil

Abstract: SUMMARY Methicillin-resistant Staphylococcus aureus (MRSA) commonly causes infection in hospitalized patients. Resistance is due to the acquisition of mecA gene located on the chromosomal element SCCmec and to date 12 types have been identified. Specific epidemic clones of MRSA have emerged with enhanced ability to spread within and among hospitals and to cross national boundaries. We studied 30 isolates from patients with MRSA infections at two hospitals in Porto Alegre city from April to December, 2008 and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
2
15
1
2
Order By: Relevance
“…However, the prevalence of SCCmec types varied between different regions [3,[25][26][27][28][29][30][31]. The Brazilian epidemic clone (BEC) carrying the SCCmec type III has been the predominant clone in several hospitals in Brazil [28,29,32]. However, in this study, a prevalence of SCCmec type II was observed, as in Caiaffa- Filho et al (2013) [30], who detected a high prevalence of this SCCmec type in a tertiary care teaching hospital in São Paulo, Brazil.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…However, the prevalence of SCCmec types varied between different regions [3,[25][26][27][28][29][30][31]. The Brazilian epidemic clone (BEC) carrying the SCCmec type III has been the predominant clone in several hospitals in Brazil [28,29,32]. However, in this study, a prevalence of SCCmec type II was observed, as in Caiaffa- Filho et al (2013) [30], who detected a high prevalence of this SCCmec type in a tertiary care teaching hospital in São Paulo, Brazil.…”
Section: Discussioncontrasting
confidence: 50%
“…These SCCmec types were also detected in MRSA surveys conducted in different Brazilian hospitals. However, the prevalence of SCCmec types varied between different regions [3,[25][26][27][28][29][30][31]. The Brazilian epidemic clone (BEC) carrying the SCCmec type III has been the predominant clone in several hospitals in Brazil [28,29,32].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, these types are commonly detected in MRSA strains associated with nosocomial infections ( Becker et al 2012 , Yamamoto et al 2012 , David et al 2013 , El-Mahdy et al 2013 ). The SCC mec type I was initially found in MRSA isolates predominantly in the UK in the 1960s.…”
mentioning
confidence: 99%
“…Furthermore, the analysis of DNA polymorphism performed in our study showed a low genetic similarity (45%) of strain BEC9393 with most of the strains studied. Researchers from southern Brazil analyzed isolates from a hospital in Porto Alegre and found the presence of SCCmec type I, which is related to the Cordoba/Chilean clone, warning of its possible spread, replacing BEC [44]. A study with blood strains collected from patients at the Hospital das Clínicas in São Paulo, Brazil, showed predominantly SCCmec type II [45].…”
Section: Discussionmentioning
confidence: 99%